Economic Valuation of Air Quality Improvement in Klang Valley: Validity and Reliability of Contingent Valuation and Benefit Transfer Methods - Afroz, Rafia (2004)
The objectives of this study are to evaluate the validity and reliability of contingent valuation method (CVM) and the validity of transferring contingent valuation estimates from a developing to a least developing country. To evaluate the impact of additional information on the willingness to pay (WTP) of the respondents, different sub samples were presented with contingent valuation scenarios offering different levels of information. One sub-sample was given the cause of ill health episodes and the policy to be implemented to remedy the cause of the ill health episodes (context version). Another sub sample was asked to value the avoidance of episodes of ill health, but was not given any details of the cause of the episodes nor the policy that would be implemented to remedy the cause of ill health episodes (non-context version).